Obsesi Tokoh Nenek Dalam Gamitan Biososiokultural pada Novel Nenek Hebat Dari Saga Karya Yoshici Shimada - Erni, Erni; Piliang, Wilda Srihastuty Handayani (GERAM: Gerakan Aktif Menulis, 2022)
The problem of natural disasters is a form of human inability to understand environmental ethics. Humans cause the tendency for natural disasters to occur. Humans, as creatures equipped with thoughts and are believed to be leaders, still violate the provisions that apply in tradition. This study aims to reveal the obsession and idealistic manifestation of women in the "Nenek" character in the novel Nenek Hebat Dari Saga by Yoshici Shimada. In addition, consider perspective and cultural perspectives. The data in this study are in the form of words, phrases, clauses, and sentences, the interpretation of which is believed to contain the values of environmental education. The data for this study came from Yoshici Shimada's children's novel, Nenek Hebat Dari Saga. The results show that there are three values of environmental education or sociocultural values contained in the novel Nenek Hebat Dari Saga by Yoshici Shimida, namely: the value of environmental education on responsibility, the value of sociocultural compassion and concern for nature; the value of not harming; the value of living simply and in harmony with nature; and the value of democratic environmental education. As a result, the obsession of the "Nenek" figure with overcoming the decline in environmental education values can be used as the foundation of sociocultural theory so that humans can live simple and ethical life. Thus, this research can provide input to teachers and parents in providing reading material to children that can raise awareness among children about the importance of preserving the environment